2021
DOI: 10.1039/d1ra00384d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granular activated carbon and Fe-modified granular activated carbon on anammox process start-up

Abstract: In this study, granular activated carbon (GAC) and Fe-modified granular activated carbon (FeGAC) prepared by ultrasonic impregnation method were added into respective up-flow anaerobic sludge blanket (UASB) reactors to explore their effects on the anammox process start-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 52 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Although activated carbon and anthracite are smaller than 2 mm, they have been widely used and proven efficient in biofiltration (Zielina, 2011) and were therefore retained in the study to maximize surface differences. Activated carbon has also been used in several AnAOB reactors to enhance AnAOB retention (Lu et al, 2021; Zhang et al, 2015). The surface area varied across media types from low surface area (sand and lava rock), to medium (expanded clay and plastic K1 carrier), to high (activated carbon).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although activated carbon and anthracite are smaller than 2 mm, they have been widely used and proven efficient in biofiltration (Zielina, 2011) and were therefore retained in the study to maximize surface differences. Activated carbon has also been used in several AnAOB reactors to enhance AnAOB retention (Lu et al, 2021; Zhang et al, 2015). The surface area varied across media types from low surface area (sand and lava rock), to medium (expanded clay and plastic K1 carrier), to high (activated carbon).…”
Section: Resultsmentioning
confidence: 99%
“…PdNA has been applied as an integrated final anoxic zone within biological nutrient removal systems (Ali et al, 2020; Ladipo‐Obasa et al, 2020; Le et al, 2019; Shi et al, 2019; Zhou et al, 2020) and in separate sludge systems (Campolong et al, 2019; Du, Cao, et al, 2019; Sharp et al, 2017; Zhang et al, 2019). So far, there are limitations in current studies of PdNA application in filters which were mostly done under synthetic conditions (Lu et al, 2021; Ma et al, 2020), unrepresentative loading rates (150‐ to 500‐g N/m 3 /day) due to small‐scale setups with exclusion of the impacts of backwash (Cao et al, 2019; Cui et al, 2020; Lu et al, 2021; Ma et al, 2020; Polli, 2019), and achieved low nitrogen removal rates (100‐ to 484‐g N/m 3 /day) (Cao et al, 2019; Cui et al, 2020; Lu et al, 2021; Ma et al, 2020; Polli, 2019) or high effluent concentrations (7‐ to 10‐mg N/L) (Cui et al, 2020; Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that anammox bacteria growth is generally slow [ 76 ], researchers try to speed up the process of adding carriers. For instance, Lu et al [ 77 ] evaluated the effects on anammox bacteria growth of the addition of GAC and Fe-modified GAC in UASB reactor finding that carriers addition can increase the aggregation of anammox microorganism and strongly reduce the start-up period of the system from 108 d to 94 d (in case of GAC) and to 83 d (in case of Fe-modified GAC).…”
Section: Resultsmentioning
confidence: 99%
“…It seemed that biochar served as a habitat for Denitratisoma which are heterotrophic denitrifying bacteria participating in nitrogen removal. Lu et al (2021) reported that the relative abundance of Denitratisoma increased in the granulated activated carbon supplemented up-flow anaerobic sludge blanket reactors compared to the control (without activated carbon). Within this framework, the relative percentage of the genus of Diaphorobacter from Comamonadaceae family which is a facultative heterotrophic denitrifier was higher in the biochar fixed biomass and particularly in the loosly–bound fraction (S1 = 0.53%; L1 = 1.3%; T1 = 0.61%) than that in suspended fraction of R0 (S0 = 0.1%).…”
Section: Resultsmentioning
confidence: 98%